Влияние начальных напряжений на квазилэмбовские моды в гидроупругих волноводах - Гузь, А.Н.; Багно, А.М. (Прикладная механика, 2020)
В данной работе для исследования распространения квазилэмбовских мод в гид роупругих волноводах, состоящих из полупространства жидкости и упругого слоя, а также из упругого полупространства и жидкого слоя, привлекаются модели предварительно напряженного тела и идеальной сжимаемой жидкости. При этом используются трехмерные линеаризованные уравнения теории упругости конечных деформаций для упругого тела и трехмерные линеаризованные уравнения Эйлера для жидкости. Предполагается, что жидкость находится в состоянии покоя. В качестве подхода выбраны постановки задач и метод, основанные на применении представлений общих решений уравнений движения идеальной сжимаемой жидкости и предварительно напряженного сжимаемого упругого тела. Досліджено поширення акустичних хвиль у попередньо деформованому стисливому пружному шарі, що взаємодіє з шаром в'язкої стисливої рідини. Результати одержано на основі тривимірних рівнянь лінеаризованої теорії пружності скінченних деформацій для пружного шару та тривимірних лінеаризованих рівнянь Нав'є - Стокса для в'язкої стисливої рідини. Застосовано постановку задачі та підхід, які базуються на використанні представлень загальних розв'язків лінеаризованих рівнянь для пружного та рідкого шарів. Одержано дисперсійне рівняння, яке описує поширення гармонічних хвиль у гідропружній системі у широкому діапазоні частот для товстого рідкого шару. Проаналізовано вплив початкових напружень, а також товщини шарів пружного тіла і рідини на фазові швидкості та коефіцієнти загасання мод Лемба. Показано, що в'язкість рідини призводить до зменшення глибини проникнення нижчої квазілембової моди в рідкий шар. The problem of quasi-Lamb waves propagation in a pre-deformed compressible elastic layer that interacts with a half-space of an ideal compressible fluid and in a predeformed compressible elastic half-space that interacts with a layer of an ideal compressible fluids is studied. The study is carried out basing on the three-dimensional linearized equations of the theory of elasticity of finite deformations for the compressible elastic solid and the three-dimensional linearized Euler equations for the ideal compressible fluid. A problem statement and an approach, based on the representations of general solutions of the linearized equations for elastic solid and fluid are used. The dispersion equations, which describe a propagation of quasi-Lamb waves in the hydroelastic systems are obtained in the wide frequency range. An effect of the initial stresses as well as the thickness of elastic layer and layer of ideal compressible fluid on the phase velocities of quasi-Lamb modes are analyzed. A criterion of existence of the quasi-Lamb waves in the hydroelastic waveguides is proposed. The developed approach and the findings make it possible to establish the limits of applicability of the models of wave processes, based on different versions of the theory of small initial deformations, as well on the classical theory of elasticity. The numerical results are presented in the form of graphs, and their analysis is given.